LIVC 적용 밀러사이클 스파크점화기관의 유동특성 연구 - 정진호; J. H. Chung; 강선제; S. J. Kang; 김진수; J. S. Kim; 정석철; S. C. Jeong; 이진욱; J. W. Lee (한국분무공학회지, 2016)
In this study, to research in-cylinder flow characteristics of spark-ignited engine with intake valve closing timing change for Miller cycle. 3D simulation study were used 6 different intake valve profile with CAD10° gap for retard intake valve closing timing. Comparison of In-cylinder flow pattern characteristic were accompanied between Base and LIVC. And the efficiency of volume and the work of compression were analyzed with simulation study. When intake valve closing angle was retarded in CAD50°, the pressure in cylinder was decreased about 12~13 bar and volume efficiency was reduced about 16%. The efficiency of volume and the work of compression were reduced on LIVC.